Resolving Systemic Financial Crisis: Policies and Institutions - Claessens, Constantijn A.; Klingebiel, Daniela; Laeven, Luc (World Bank, Washington, D.C., 2013)
The authors analyze the role of institutions in resolving systemic banking crises for a broad sample of countries. Banking crises are fiscally costly, especially when policies like substantial liquidity support, explicit government guarantees on financial institutions liabilities, and forbearance from prudential regulations are used. Higher fiscal outlays do not, however, accelerate the recovery from a crisis. Better institutions less corruption, improved law and order, legal system, and bureaucracy do. The authors find these results to be relatively robust to estimation techniques, including controlling for the effects of a poor institutional environment on the likelihood of financial crisis and the size of fiscal costs. Their results suggest that countries should use strict policies to resolve a crisis and use the crisis as an opportunity to implement medium-term structural reforms, which will also help avoid future systemic crises.